Clinical difference between fibroblast growth factor receptor 2 subclass, type IIIb and type IIIc, in gastric cancer - Masakazu Yashiro (Nature Portfolio, 2021)
Abstract Fibroblast growth factor receptor 2 (FGFR2) has two isoforms: IIIb type and IIIc type. Clinicopathologic significance of these two FGFR2 subtypes in gastric cancer remains to be known. This study aimed to clarify the clinicopathologic difference of FGFR2IIIb and/or FGFR2IIIc overexpression. A total of 562 patients who underwent gastrectomy was enrolled. The expressions of FGFR2IIIb and FGFR2IIIc were retrospectively examined by immunohistochemistry or fluorescence in situ hybridization (FISH) using the 562 gastric tumors. We evaluated the correlation between clinicopathologic features and FGFR2IIIb overexpression and/or FGFR2IIIc overexpression in gastric cancer. FGFR2IIIb overexpression was observed in 28 cases (4.9%), and FGFR2IIIc overexpression was observed in four cases (0.7%). All four FGFR2IIIc cases were also positive for FGFR2IIIb, but not in the same cancer cells. FGFR2IIIb and/or FGFR2IIIc overexpression was significantly correlated with lymph node metastasis and clinical stage. Both FGFR2IIIb and FGFR2IIIc were significantly associated with poor overall survival. A multivariate analysis showed that FGFR2IIIc expression was significantly correlated with overall survival. FISH analysis indicated that FGFR2 amplification was correlated with FGFR2IIIb and/or FGFR2IIIc overexpression. These findings suggested that gastric tumor overexpressed FGFR2IIIc and/or FGFR2IIIb at the frequency of 4.9%. FGFR2IIIc overexpression might be independent prognostic factor for patients with gastric cancer.